2013
DOI: 10.1155/2013/783715
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Potential Issues and Challenges in MR Imaging

Abstract: Magnetic resonance imaging is a noninvasive technique that has been developed for its excellent depiction of soft tissue contrasts. Instruments capable of ultra-high field strengths, ≥7 Tesla, were recently engineered and have resulted in higher signal-to-noise and higher resolution images. This paper presents various subsystems of the MR imaging systems like the magnet subsystem, gradient subsystem, and also various issues which arise due to the magnet. Further, it also portrays finer details about the RF coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
(16 reference statements)
0
17
0
Order By: Relevance
“…Abbreviations used: 2D/3D, two−/three-dimensional; FoV, field of view; MRI, magnetic resonance imaging; RF, radiofrequency; ROI, region of interest; SNR, signalto-noise ratio Birdcage coils provide uniform excitation (B 1 + ) and reception (B 1 − ) magnetic fields within their internal volume. 7 The areas of field homogeneity provided by such coils are sufficient for small-animal, whole-body imaging, even at high frequencies, where the wavelength of the radiofrequency (RF) field used shortens, leading to uniformity issues in human MRI. 8 The downside of the use of volume coils is the low sensitivity that they provide and the large area from which they collect noise.…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations used: 2D/3D, two−/three-dimensional; FoV, field of view; MRI, magnetic resonance imaging; RF, radiofrequency; ROI, region of interest; SNR, signalto-noise ratio Birdcage coils provide uniform excitation (B 1 + ) and reception (B 1 − ) magnetic fields within their internal volume. 7 The areas of field homogeneity provided by such coils are sufficient for small-animal, whole-body imaging, even at high frequencies, where the wavelength of the radiofrequency (RF) field used shortens, leading to uniformity issues in human MRI. 8 The downside of the use of volume coils is the low sensitivity that they provide and the large area from which they collect noise.…”
Section: Introductionmentioning
confidence: 99%
“…This is most often a superconducting electromagnet but it could also be a permanent magnet. Added to this is a coil to generate the radiofrequency electromagnetic field (the “RF field”) and, lastly, there are the imaging gradient coils, responsible for creating the spatial‐encoding magnetic fields and typically referred to as “the gradients.” While essential in allowing the MRI device to produce images, these coils and the manner in which the fields they generate interact with matter can also, at times, be the cause of serious threats to human life and limb …”
mentioning
confidence: 99%
“…While essential in allowing the MRI device to produce images, these coils and the manner in which the fields they generate interact with matter can also, at times, be the cause of serious threats to human life and limb. [1][2][3][4][5][6][7][8][9][10] This article explores the physics underlying the safety risks associated with the three principal types of coils and magnets. A number of other reviews and expos es exist that cover the basic physics behind the interactions of one or more of these and are recommended as supplemental reading.…”
mentioning
confidence: 99%
“…Also, it can be witnessed that the false-positive ratio gets minimized to 18 percent.Electronics 2020, 9, 45 2 of 13 be observed that enabling technologies for smart tire quality assessment for realizing intelligent tire manufacturing has been gaining prominence to address challenges such as automated tire defects detection.Generally, it can be witnessed that in the modern-day scenario, there is a humongous and swift growth in the gadgets, equipment, and devices connected to the internet. These devices, gadgets, and equipment have profound computing characteristics, and at the same time, they are exceedingly performance-oriented [2]. Due to all these facts, the concept of deep learning has evolved into a newer dimension, and it plays a significant part in processing and recognizing images, speech, and video, and so on.…”
mentioning
confidence: 99%
“…Generally, it can be witnessed that in the modern-day scenario, there is a humongous and swift growth in the gadgets, equipment, and devices connected to the internet. These devices, gadgets, and equipment have profound computing characteristics, and at the same time, they are exceedingly performance-oriented [2]. Due to all these facts, the concept of deep learning has evolved into a newer dimension, and it plays a significant part in processing and recognizing images, speech, and video, and so on.…”
mentioning
confidence: 99%